Hubungan Karakteristik Ibu Bersalin dengan Kejadian Plasenta Previa di Klinik Pratama Afisyah Kabutapen Deli Serdang Provinsi Sumatera Utara Tahun 2021-2023 - Erin Padilla Siregar; Sri Rezeki; Amelia Erawaty Siregar; Mesrida Simarmat (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Placenta previa is a placenta that is abnormally located, namely in the lower segment of the uterus so that it covers part or all of the internal uterine ostium. Based on data obtained by the World Health Organization (WHO) in 2008, quoted by Wahyu 2019, the prevalence of placenta previa is around 458 out of 100,000 births each year, while the prevalence of placenta previa according to WHO in 2009 is around 320 out of 100,000 births. This type of research is descriptive and aims to find out the relationship between the characteristics of mothers giving birth and the incidence of placenta previa at Pratama Afisyah Clinic. This research instrument is the medical record. Editing, coding, data entry, tabulating and analyzing data. The research results from 103 respondents, the majority of birth mothers who experienced bleeding were 79 respondents (76.7%), the minority who did not experience bleeding were 24 respondents (23.3%). The majority at risk age were 77 respondents (74.8), the majority at risk parity were 91 respondents (88.3), the majority had a history of SC delivery as many as 79 respondents (76.7%). From the results of the statistical tests, the Odd ratio (OR) = 3.500 was obtained. 95% CI = 1.196-10.240 and P value 0.032 < 0.05, which means there is a significant relationship between maternal age characteristics and the incidence of placenta previa. The results of the statistical test obtained an Odd ratio (OR) = 0.121. 95% CI = 0.015-0.979 and P value 0.026 < 0.05, which means there is a significant relationship between maternal parity characteristics and the incidence of placenta previa. The results of the statistical test obtained an Odd ratio (OR) = 0.350. 95% CI = 0.137-0.895 and P value 0.046 < 0.05, which means there is a significant relationship between the characteristics of the mother's birth history and the incidence of placenta previa. For mothers who give birth with placenta previa, to further increase knowledge about placenta previa by knowing the causes and impacts.